PENGARUH LINGKUNGAN PENGENDALIAN TERHADAP FRAUD PADA LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PAREPARE - Jumriani, Jumriani; Anwar, Anwar (Economos : Jurnal Ekonomi dan Bisnis, 2019)
The Government Internal Control System (GICS), which is considered weak and inappropriate, can commit fraud. The author takes the title "The Effect of Control Environment on Fraud in the Report on Local Government Finances of Parepare City".This research was conducted with the aim of finding out whether or not the influence of the controlenvironmenton organizational structure and human resource policy variables on fraud in the Report on Local Government Finances of Parepare City. The purpose of this study is expected to provide insight, knowledge about the detection of indications of fraud in the report on local government finances and provide evidence of control environment influences in the government internal controls that can provide opportunities for financial statement fraud. The research method used is quantitative descriptive method. To obtain the results of this study, researchers conducted data collection at the Regional Secretariat of Parepare City by distributing one questionnaire to each employee, then the data obtained were processed using the SPSS For Windows Version 21 application with data processing techniques, namely multiple linear regression.The results of this study indicate that the control environment in the organizational structure policy has a positive effect on efforts to detect indications of fraud in the Human Resources Agency (HRA) of Parepare City.The influence of the control environment in human resource policies has a significant influence on efforts to detect indications of fraud.